2012
DOI: 10.4161/cc.21611
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the protein interaction between FAK and IGF-1R inhibits melanoma tumor growth

Abstract: FAK (focal adhesion kinase) and IGF-1R (insulin-like growth factor receptor-1) directly interact with each other and thereby activate crucial signaling pathways that benefit cancer cells. Inhibition of FAK and IGF-1R function has been shown to significantly decrease cancer cell proliferation and increase sensitivity to chemotherapy and radiation treatment. As a novel approach in human melanoma, we evaluated the effect of a small-molecule compound that disrupts the protein interaction of FAK and IGF-1R. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Previously, we have shown that INT2-31 penetrates tumor cells in vitro and can be identified in the tumor xenograft in vivo [30]. The additive effect of INT2-31 with gemcitabine, for inducing apoptosis and inhibiting tumor growth, demonstrates the possible use of INT2-31 in combination with standard chemotherapeutic regimens for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we have shown that INT2-31 penetrates tumor cells in vitro and can be identified in the tumor xenograft in vivo [30]. The additive effect of INT2-31 with gemcitabine, for inducing apoptosis and inhibiting tumor growth, demonstrates the possible use of INT2-31 in combination with standard chemotherapeutic regimens for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, allosteric FAK inhibitor Y15, targeting major autophosphorylation site of FAK Y397, which affects not only FAK kinase activity but, more importantly, FAK interactions with Src and PI3K, showed promising results in treatment of breast, pancreatic, colon and glioblastoma cancers [49]. PPI inhibitor NT2-31 targeted to the FAK-IGF-1R site of interaction dramatically reduced growth of melanoma, pancreatic and gastric cancers and show synergy with chemotherapy [22, 50]. …”
Section: Discussionmentioning
confidence: 99%
“…All staining procedures were done as previously described [50]. For detection, we used Vectastain Elite ABC kit (Vector Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…58 Similarly, in melanoma, FAK interaction with the insulin-like growth factor receptor-1, IGF-1R, is necessary for downstream phosphorylation of Akt. 59 Abrogation of the FAK/IGF-1R interaction led to melanoma regression in an orthotopic mouse model. 59 Furthermore, in glioblastoma, FAK activity is dependent on PI3K/Akt activation, since knockdown of either the PIK3CA or PIK3R1 gene reduces FAK phosphorylation and tumor cell-invasive properties.…”
Section: Focal Adhesion Kinase (Fak) In Normal Skinmentioning
confidence: 99%
“…59 Abrogation of the FAK/IGF-1R interaction led to melanoma regression in an orthotopic mouse model. 59 Furthermore, in glioblastoma, FAK activity is dependent on PI3K/Akt activation, since knockdown of either the PIK3CA or PIK3R1 gene reduces FAK phosphorylation and tumor cell-invasive properties.…”
Section: Focal Adhesion Kinase (Fak) In Normal Skinmentioning
confidence: 99%